Wireless sensor network platform for monitoring the industrial apparatus - Bhautik Patil; Supriya Mahajan; Pratiksha Sawarkar (International Journal of Innovations in Engineering Research and Technology, 2021)
Wireless Sensor Networks (WSNs) are one of the fastest gr owing and emerging technologies in the field of Wireless networking. WSNs have a vast amount of applications inc luding environmental monitoring, oil and gas, agriculture, inventory control, robotics and health care. Thi s paper focuses on monitoring and protection of oil and water operations using WSNs that are optimized to decre ase installation, and maintenance cost, energy requirements, increase reliability and improve communic ation efficiency. Such model could provide new tools for research in predictive maintenance and condition-base d monitoring of factory machinery in general and for open architecture machining system in particular.